Atmospheric correction of CHRIS/PROBA data acquired in the SPARC campaign - Guanter, L; Alonso, L; Moreno, J (2004)
An atmospheric correction algorithm for satellite/airborne data taken over land has been implemented. The algorithm is designed to obtain the main atmospheric parameters needed in the correction from the image itself, so an optimal characterization of the atmospheric state, in temporal and spatial resolution terms, is achieved. The results of the application to CHRIS/PROBA data from the ESA SPARC campaign is presented in this work, focusing on the validation of both the final surface reflectance and the intermediate atmospheric water vapor and aerosol products. A final step devoted to the recalibration of the obtained reflectances is needed, due to calibration problems in the near-infrared CHRIS bands. The comparison with coincident MERIS data provides a final validation of the surface reflectance image.